Optimization of Microsoft Excel as a Data Processing Tool for Letter Making in Indonesian Correspondence Learning - Dian Fithra Permana; Nina Oktarina; Anis Susanti (Universitas Negeri Semarang, 2025)
This study aims to optimize the use of Microsoft Excel as a data processing tool in making letters in learning Indonesian correspondence. Learning Indonesian correspondence, which involves the skill of writing official and personal letters, often faces challenges in terms of time efficiency and difficulties in organizing information. Microsoft Excel, with its data processing and template creation features, is believed to help simplify and speed up the process of creating letters. This research was conducted using an experimental method with a total of 106 student respondents in the Office Administration Education study program, State University of Semarang, involving two groups: an experimental group with a total of 53 students using Microsoft Excel and a control group with a total of 53 students who used the manual method in making letters. The results showed that students who used Excel were more efficient in completing letter-making tasks, with an average shorter letter-making time compared to the control group. In addition, the quality of the letters produced by the experimental group is also better, with a more structured and rule-based format. The results of the questionnaire and observation showed that the majority of students felt helped by the use of Excel, although there were several obstacles faced related to understanding formulas and formatting settings. Overall, Microsoft Excel can be optimized in correspondence learning to improve students' efficiency, quality, and skills in letter creation.